Performance evaluation of corrosion inhibitors for use in concrete structures - Srinivasan, P.; Chellappan, A. (Journal of Structural Engineering, 2024)
Corrosion in reinforced/pre-stressed concrete structure is a common durability problem with respect to chloride induced corrosion. Several methods are practiced for enhancing the service life of reinforced concrete structure with respect to chloride induced corrosion. These include concrete coatings, fusion bonded epoxy bars, galvanized steel bars, use of corrosion inhibitors etc., Each of the method has its own advantages and disadvantages. For example, the application of concrete coating needs surface preparation and also it cannot be applied in highly humid conditions. The use of corrosion inhibitor appears to be an effective and simple method in protecting the reinforcement from corrosion. This paper highlights the accelerated tests carried out in SERC and its findings on the evaluation of a corrosion inhibitor in chloride environment. Different dosage of inhibitors were considered and the time delay in giving additional protection due to the addition of inhibitor has been arrived. It has been found that the inhibitor provides higher chloride tolerance and also reduced weight loss in the reinforcement. The accelerated method adopted in this study provides an easy approach for the performance evaluation of corrosion inhibitor for use in concrete.